Magazine children (1930/1950) (Educação e Pesquisa, 2000)
The Brazilian magazines Domestic Life and Fon-Fon! published between 1930 e 1950 different materials about childhood: texts, pictures, caricatures, illustrative drawings etc. This article analyzes some of those photographic images, discussing their thematic fields and some analysis procedures that contributed to the characterization of children within the Brazilian social universe by those periodicals. The children represented in them were, in their majority, white and they possessed structured family lives (father, mother) and a privileged social situation. The children's pictures, in some circumstances, were produced at photographic studios and they highlighted the beauty and happiness. Their clothes and accessories helped to compose the image of well-off and happy children. The universe of photography in the childhood is articulated to other constant concerns when speaking about children: health, education, religiosity, leisure and fashion. Pictures of institutions such as, for instance, playgrounds assume characteristics different from those described previously. In that case, the children were photographed collectively as an advertisement of the activities developed by the institutions. Considering the picture as a social production, and avoiding, therefore, to conceive it as a reflex of the real, the article tries to articulate texts and images, as well as to consider different possibilities of the child's world.